PENERAPAN RANGE OF MOTION (ROM) PADA PASIEN STROKE DENGAN GANGGUAN MOBILITAS FISIK DI WILAYAH KERJA PUSKESMAS PAMPANG KOTA MAKASSAR PUSKESMAS PAMPANG - Arni Arni; Akbar Asfar; Brajakson Siokal; Mardiah (Jurnal Kesehatan, 2026)
STROKE is one of the major health problems in Indonesia because it not only increases morbidity and disability rates but also reduces patients' quality of life. Physical mobility impairment is one of the common effects on post-stroke patients due to muscle weakness and limited range of motion. One nursing intervention that can be provided to reduce these effects is Range of Motion (ROM) exercises, which have been proven to maintain joint flexibility, increase muscle strength, and prevent complications from immobilisation. To determine the application of ROM in stroke patients with physical mobility disorders in the working area of the Pampang Community Health Centre in Makassar City. A case study was conducted through nursing care that included the stages of assessment, nursing diagnosis, planning, implementation, and evaluation. The intervention was carried out for three days (3x24 hours) on patient Mr. B, a 66-year-old male with a history of non-haemorrhagic stroke since 3 years ago who experienced weakness in his right extremities. The results showed that after ROM exercises, the patient experienced improved mobility, characterised by reduced muscle stiffness, increased limb strength, and increased range of motion. Daily evaluations showed that the problem of physical mobility impairment had been partially resolved, with the involvement of the family playing an important role in helping with the exercises at home. The application of ROM is effective in improving the mobility of stroke patients, preventing complications due to immobilisation, and supporting patient independence. ROM exercises are a simple, inexpensive intervention that can be performed independently by patients and families, so they are recommended for routine application both in health facilities and at home.